Reconstructing the Sundanese radio folktale for the multimedia theater and film - Dedi Warsana; Hery Supiarza; Erik Muhammad Pauhrizi (Gelar: Jurnal Seni Budaya, 2026)
By utilising the framework of Adaptation Studies and Participatory Action Research (PAR), this study examines the intermedial adaptation of the Sundanese radio folktale Si Rawing into the multimedia theatre performance Tilu Si Rawing Makalangan. The project investigates how the cultural significance of classical auditory storytelling may be preserved while being recontextualised via digital performance, taking into consideration the changing media environment that has resulted in the fall of radio theatre and the emergence of digital platforms. In a theoretical sense, the research draws on Hutcheon's concept of adaptation as re-interpretation and Kattenbelt's idea of intermediality in order to explore the relationship between sound, imagery, and embodiment in the process of transformation across media. In terms of methodology, Participatory Action Research (PAR) made it possible for a creative process that was collaborative to take place. This process involved academics, theatre artists, and radio practitioners working together in iterative cycles of planning, action, observation, and reflection. The findings demonstrate that adaptation functions not as a medium transfer but rather as a dramaturgical reconstruction. In this reconstruction, the structural inadequacies of the radio script were reinterpreted in order to emphasise psychological conflict, spatial-temporal coherence, and audience immersion. The digital liveness that resulted from the integration of filmic projections, dance, and live performance has reawakened the imaginative possibilities that were formerly present in radio narrative. By suggesting an epistemic model of cultural revitalisation that connects local oral traditions and digital performance aesthetics in the Indonesian context, the study makes a contribution to contemporary discourse on adaptation and intermedial performance.